Genetic dissection of yield and yield-related traits in mungbean based on QTL meta-analysis - Du, Binbin; Wang, Qifei; Gao, Song; Yang, Fan; Zhang, Lei; Zhang, Xiao; Huo, Dongao; Wu, Jia; Zhang, Xingen; Li, Fang; Lu, Baowei; An, Fengxia (Frontiers in Genetics, 2025)
As an important food crop and nutritional source, mungbean has prioritized yield improvement as a key objective in breeding programs. In present study, we conducted a QTL meta-analysis to integrate 660 QTLs related to yield and yield-related traits in mungbean published over the past 20 years. A total of 590 initial QTLs were mapped onto a high-density consensus map, resulting in the identification of 72 meta-QTLs (MQTLs). These MQTLs were unevenly distributed across 11 linkage groups (LGs) with an average confidence interval (CI) of 1.21 cM, which was 6.26-fold narrower than the average CI of the initial QTLs. Among these 72 MQTLs, 20 were validated in a genome-wide association study (GWAS) for yield and yield-related traits in mungbean. Orthologous MQTL analysis revealed that 22 mungbean MQTLs were collinear with 19 MQTLs in common bean for yield and yield-related traits. In addition, 20 breeder’s MQTLs were screened from the 72 MQTLs, and 339 gene models were identified within the breeder’s MQTL regions. Twenty-two mungbean orthologs of yield-related genes such as seed germination, tiller number, and plant height in rice and Arabidopsis were identified in the breeder’s MQTL regions using homology analysis. This study contributes to understanding the genetic mechanisms for yield and yield-related traits and provides new ideas for the genetic improvement and breeding of mungbean.